AI and the Future of Journalism: Perception of Pakistani Journalists on the Opportunities and Limitations of ChatGPT - Ahmed, Rabeeia; Abbasi, Waseem Ahmed; Shakil, Hira (Journal of Peace, Development and Communication, 2024)
Generative AI marks the beginning of a revolution in journalism and media content development. One such technology that is transforming the journalism field is ChatGPT. This research article attempts to analyze the capacity and limitations of ChatGPT and offers reflections on the implications of generative AI for journalists. It also examines the perception of Pakistani journalists regarding the opportunities and limitations of the software. The research has four major objectives; to investigate the knowledge of journalists regarding ChatGPT, to investigate the perception of journalists towards the opportunities and limitations of ChatGPT, to examine the extent of usage of the software among Pakistani journalists; and lastly to determine if Pakistani journalists favor the use of AI tools in content creation. A questionnaire was used to collect data from working journalists associated with different media organizations in the country, including reporters, editors, producers, anchors and freelance journalists etc. Data source for the study includes 200 Pakistani working journalists from local, national and international media as well as free-lance journalists. The findings indicate that according to the perception of Pakistani journalists, AI softwares usually hallucinates data which can lead to misinformation. The study also revealed that the human agency is required to use these apps effectively. They also believe that proper training is required for journalists so that they can use these apps to enhance their functioning instead of using it as a substitute.